Front cover: Metabotypes Related to Meat and Vegetable Intake Reflect Microbial, Lipid and Amino Acid Metabolism in Healthy People. Issue 21 (5th November 2018) - Wei, Runmin; Ross, Alastair B.; Su, MingMing; Wang, Jingye; Guiraud, Seu‐Ping; Draper, Colleen Fogarty; Beaumont, Maurice; Jia, Wei; Martin, Francois‐Pierre
Abstract : Mol. Nutr. Food Res. 2018, 62, 1800583 DOI:10.1002/mnfr.201800583 Epidemiological evidence suggests that habitual intake of plant‐based diets reduces the risk of metabolic disorders. In article number1800583, Wei Jia, Francois‐Pierre Martin, and co‐workers develop a methodology to identify the relationship between dietary patterns and metabolites indicative of food intake and metabolism in a heterogeneous population. Several metabolites previously associated with health risk factors are found to be negatively associated with vegetable dietary intake. The cover image shows a sparse canonical correlation network of high meat/vegetable intakes with different urinary and blood metabolic fingerprints.